Optimizing wireless power transfer efficiency at 13.56 MHz using double negative metamaterials - Misran, Mohamad Harris; Misran, Mohamad Harris; Meor Said, Maizatul Alice; Othman, Mohd Azlishah; Salleh, Azahari; Ramlee, Ridza Azri; Abdul Rahim, Sharul Kamal; Idris, Mohd Zahid (Electromagnetics Academy, 2025)
Recent advancements and innovations in wireless power transfer (WPT) technology have led to an increased demand for systems with high power transfer efficiency (PTE) and extended transmission distances to meet the needs of end users. However, many existing WPT systems suffer from limited PTE and restricted transmission ranges due to their reliance on inductive coupling. A significant drawback of inductive coupling is the sharp decline in PTE as the distance between the transmitter and receiver coils increases. To address these limitations, this study proposes the design of an inductive WPT system enhanced by the integration of metamaterials (MTMs) to improve PTE through magnetic field manipulation. By strategically positioning MTMs between the transmitter (Tx) and receiver (Rx) coils, the efficiency and range of WPT systems can be significantly enhanced. MTMs exhibit unique properties, such as negative refraction and evanescent wave amplification, which are particularly promising for improving PTE in WPT systems. At a separation distance of 70 mm, the implementation of negative permittivity MTMs and double-negative MTMs yields a remarkable improvement in PTE, achieving an increase of 180% compared to a conventional WPT system without MTM integration. Systems with MTM maintain better PTE at increasing lateral and angular misalignments, but at 90° misalignment, power transfer is almost impossible, even with MTM, due to complete misalignment of the fields.This study aims to provide a comprehensive analysis of the development and performance of negative permittivity and double-negative MTM-based WPT systems, offering critical insights into their potential for enhancing WPT efficiency and range.